Poster 142: Identifying the Bony and Soft Tissue Mechanisms Responsible for Glenohumeral Internal Rotation Range of Motion. Issue 7 (30th July 2022) - Erickson, Brandon; Cohen, Steven; Ciccotti, Michael; Hefta, Michael; Buchheit, Paul; Rauch, Joseph; Fcasni, Shawn; Plum, Alexander; Hoback, Aaron; Thomas, Stephen; Paul, Ryan
Objectives: Shoulder and elbow injuries account for about one-fourth of the total injuries in professional baseball players. The loss of shoulder internal rotation range of motion (IR ROM) has been identified as a significant risk factor for upper extremity injuries in pitchers across all ages. Several anatomic structures have been independently associated with IR ROM. First, greater amounts of humeral retroversion (HR) have been related to decreased IR ROM. Second, increased posterior capsule thickness (PCT) has also been related to decreased IR ROM. Lastly, adaptations to the teres minor muscle pennation angle (PA) has been related to losses in IR ROM and the PA of both the infraspinatus and teres minor have been related to the acute decrease in IR ROM following pitching. However, these three anatomic structures have not been collectively measured in baseball pitchers to determine the underlying mechanisms responsible for IR ROM. Therefore, this study will determine the contributions of HR, PCT, and posterior rotator cuff PA on IR ROM in healthy professional baseball pitchers. We hypothesized that HR, PCT, and posterior rotator cuff PA would have a significant contribution to IR ROM. Methods: 51 healthy professional pitchers were recruited for this cross-sectional study at the beginning of the 2021 Major League Baseball spring training. Participants received a bilateral IR ROM assessment while laying supine with the shoulder at 90 degrees of abduction and the scapula stabilized. Ultrasound imaging was also performed bilaterally to assess HR, PCT, infraspinatus (superficial + deep) PA, and teres minor (superficial + deep) PA. All ultrasound imaging was performed utilizing a previously published standardized technique. A stepwise regression was performed which included both arms to determine the mechanisms of IR ROM. Results: The first variable to enter into the stepwise regression model was HR which had a moderate relationship with IR ROM (regression coefficient of -0.502). PCT also entered the model, as measuring both HR and PCT improved the relationship with IR ROM from moderate to strong (regression coefficient of -0.657). Infraspinatus and teres minor PA did not enter the predictive model of IR ROM. Conclusions: HR and PCT were found to be the primary anatomic mechanisms responsible for glenohumeral IR ROM. Surprisingly, the posterior rotator cuff PA was not found to be a significant predictor of IR ROM. The posterior rotator cuff may instead contribute more to the acute decrease in IR ROM following pitching, which has recently been reported. As deficits in IR ROM can have harmful effects in baseball pitchers, understanding which anatomic structures are most responsible for IR ROM is important for injury prevention and treatment. Figure 1. Ultrasound image of the infraspinatus, with yellow arrows indicated the superficial infraspinatus pennation angle and green arrows representing the deep infraspinatus pennation angle. CT=central tendon, SN=suprascapular notch. Table 1. Standardized regression coefficients and regression strengths of included and excluded variables in the internal rotation range of motion model.